A New Cytotoxic Friedelane Acid – Pluricostatic Acid – and Other Compounds from the Leaves of Marila pluricostata - Olmedo, Dionisio A. (Molecules, 2008)
Bioassay-guided fractionation of the dichloromethane extract of the leaves of Marila pluricostata led to the isolation of 2α,3β-dihydroxy-D:A-friedoolean-28-oic acid (pluricostatic acid), a new friedelane triterpenoid, (1), ten known triterpenoids and three sterols. Their chemical structures were elucidated through spectroscopic analysis. The less polar fractions, on GC/MS analysis and comparison with a MS library, resulted in the identification of twenty four sesquiterpenoids. The new triterpenoid acid 1 showed cytotoxicity against the MCF-7, H-460, and SF-268 human cancer cell lines with GI(50) values from 1.2 to 3.3 μg/mL.